2022
DOI: 10.2340/jrm.v54.2209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Feedback During Balance Training on Knee Function and Balance Ability in Postoperative Patients After Knee Fracture: A Randomized Controlled Trial

Abstract: Objective: To investigate the effects of visual feed­back training on knee function and balance ability in postoperative patients with knee fracture. Methods: A clinical randomized controlled trial with 104 participants, randomly assigned (1:1) to a visual feedback training group or a control group. Eligible participants were evaluated using Lysholm scores, the Tinetti scale, and the evaluation module of TecnoBody to demonstrate dynamic balance fun­ction in a standing position before treatment and after 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The detected significant improvement in the symmetry index after the VFB treatment is in agreement with the findings of Zhang et al [18] and Christensen et al [31]. These authors found, respectively, an improvement in the Tinetti clinical score in postoperative patients with a knee fracture at 8 weeks after treatment, and an immediate improvement in the gait characteristics (interlimb symmetry) during a high-demand walking task in a patient after a TKR [18]. The symmetry index is one of the most important parameters to measure the gait and kinematic pattern alterations [32,33].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The detected significant improvement in the symmetry index after the VFB treatment is in agreement with the findings of Zhang et al [18] and Christensen et al [31]. These authors found, respectively, an improvement in the Tinetti clinical score in postoperative patients with a knee fracture at 8 weeks after treatment, and an immediate improvement in the gait characteristics (interlimb symmetry) during a high-demand walking task in a patient after a TKR [18]. The symmetry index is one of the most important parameters to measure the gait and kinematic pattern alterations [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…It is still debated that in the post-operative TKR, the damaging of the proprioceptors and the changes in the articular structure can further affect the lower limb stability and balance function, already altered by OA, resulting in a loss of the precise control of the effector because the bilateral proprioceptive receptor's afferent information is asymmetrical [18]. Some authors point out that the model of prosthesis chosen has an influence on the proprioception, due to the alteration of the articular environment and structures as the cruciate ligament, meniscus, and intracapsular mechanoreceptors, that are essential in providing proprioceptive reflexes [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While new technological tools have been shown to be efective, either alone [28] or in combination with classical protocols [29], in improving the physiological and cognitive aspects that allow the maintenance of a healthy state over time (e.g., by improving postural control and preventing falls), the efectiveness of these technologies in promoting PA, especially in older populations, is still unclear.…”
Section: Introductionmentioning
confidence: 99%